PROBLEMATYKA BADAŃ DOTYCZĄCYCH POSTAW WOBEC UCZENIA SIĘ JĘZYKÓW OBCYCH NA PRZYKŁADZIE JĘZYKA HISZPAŃSKIEGO - Spychała-Wawrzyniak , Małgorzata (Neofilolog, 2020)
Attitudes, including beliefs, values, and motivation are within the scope of interest of numerous fields of study such as psychology, philosophy, sociology, and anthropology. In psychology, attitudes related to affective, cognitive and, in particular, behavioral reactions are studied. It is believed that attitudes do not only affect the behavior of the individual, but also their ways of evaluating specific actions. At the same time, empirical research in this area is extremely problematic and conditioned by many individual differences (e.g. age, gender, place of residence, personality traits, etc.). On the other hand, in glottodidactics, the common trend in this type of research is analysis of students' attitudes (including motivation) towards a foreign language and its culture(s). The purpose of the article is to briefly present the methodology of research on attitudes towards learning different languages. First, we review the concepts of attitudes, beliefs, values, and motivation from a psychological and didactic perspective. We also focus our attention on the types of attitude measurement used (which include motivation). Finally, we present some results of research conducted for the first time in Poland in the field of attitudes and motivation of secondary school students towards learning Spanish.